Syncretism And Migration In Uzbek Linguistics - Tojiyev Alimjon Muydinovich (Global Scientific Publishing, 2024)
the issue of migration in world and Russian linguistics has also found expression in the scientific theoretical views of Uzbek linguists. Our linguists studied the phenomenon of displacement in relation to various linguistic phenomena. However, no analysis related to the concept of syncretism has been done.
Keywords: migration issue; theoretical view; Uzbek linguistics